(untitled) (Research, Society and Development, 2025)
Fracture of endodontic instruments is a frequent challenge during root canal treatment and represents a significant complication for the clinician. This study aimed to critically review the main methods of fractured instrument removal, reporting their indications, advantages, limitations, and scientific evidence. The methodology consisted of an integrative literature review, selecting articles indexed in PubMed, Scopus, and SciELO, prioritizing publications between 2010 and 2025. The results of this review indicated that ultrasonics combined with the aid of an operating microscope is the first-choice technique for fragments located in the coronal and middle thirds, whereas static or dynamic endodontic guides are indicated in complex cases, such as curved canals or apical fragments, as they provide directed preparation and greater dentin preservation. Tube systems remain a secondary option, recommended only when less invasive approaches fail, due to their greater root dentin removal. In extreme cases, the bypass technique may be considered as a last resort, allowing partial canal de-obstruction and maintenance of tooth function. Technologies such as GentleWave® and AReneto® are presented as promising solutions to diversify and improve therapeutic alternatives; however, they still lack sufficient clinical evidence to confirm their effectiveness. It is concluded that no universally superior technique exists for all cases, and clinical decision-making should be individualized, guided by the principle of minimal intervention and the operator’s experience, in order to optimize clinical outcomes, reduce complications, and preserve tooth structure to the greatest extent possible.